Default on Joint Responsibility Agreements by Debtors - Abdullah, Windi Friliani; Junus, Nirwan (Damhil Law Journal, 2023)
The purpose of this study is to find out how the arrangement of the joint responsibility system in the lending and borrowing agreement at PNM Mekaar East City Branch 2 Gorontalo City and to find out the legal consequences and efforts to resolve defaults in joint responsibility agreements by debtors in Huangobotu Village. The research method used is Normative legal research. The data obtained are primary and secondary data. The data collection techniques used by the author are observation, interview, and literature. The results of the study show that the arrangement regarding the joint responsibility system in the loan and borrowing agreement at PNM Mekaar Branch Kota Timur 2 Gorontalo City is in accordance with the provisions of the applicable rules as stated in Article 1278 of the Civil Code concerning joint responsibility or joint responsibility where the joint responsibility agreement can occur over the will or agreement of the parties and must be expressly stated in the agreement. And the type of joint responsibility that is applied by business groups in the village of Huangobotu is a type of passive joint responsibility as stated in Article 1280 of the Civil Code. And the legal consequences of default in the lending and borrowing agreement with a joint responsibility system at PNM Mekaar East City 2 Branch City of Gorontalo in Huangobotu Village are payment of achievements by each group member, and requests for fulfillment of achievements by PNM Mekaar East City 2 Branch of Gorontalo City to the person in charge of customers who do not fulfill these obligations. And efforts to resolve defaults by PNM Mekaar Branch Kota Timur 2 Kota Gorontalo are more to the approach of deliberation or mediation with customers to find the right settlement solution.